2016
DOI: 10.1097/igc.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

European Society of Gynecological Oncology Statement on Fibroid and Uterine Morcellation

Abstract: Recently, there has been an intense discussion about the issue of fibroid and uterine morcellation in relation to the risk of unrecognized uterine sarcoma spread. Morcellation can negatively influence the prognosis of patients, and transecting the specimen into pieces prevents the pathologist from performing proper disease staging. Many societies have published their statements regarding this issue. The European Society for Gynecological Oncology has established a working group of clinicians involved in diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 21 publications
0
42
0
3
Order By: Relevance
“…Advances in the operative techniques resulted in the development of a special intraperitoneal bag to prevent uncontrolled tissue dissemination during morcellation. Additionally, recommendations of the European Society of Gynecological Oncology on fibroid and uterine morcellation resulted in subsequent increase (by 262.2%) in the number of SLH in 2016 [21,22]. Reports from the literature showed that careful preoperative counseling further reduces the risk of unexpected malignancies in the uterus and confirmed safety of morcellation in selected group of patients [23].…”
Section: Discussionmentioning
confidence: 97%
“…Advances in the operative techniques resulted in the development of a special intraperitoneal bag to prevent uncontrolled tissue dissemination during morcellation. Additionally, recommendations of the European Society of Gynecological Oncology on fibroid and uterine morcellation resulted in subsequent increase (by 262.2%) in the number of SLH in 2016 [21,22]. Reports from the literature showed that careful preoperative counseling further reduces the risk of unexpected malignancies in the uterus and confirmed safety of morcellation in selected group of patients [23].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, morcellation of the specimen in an enclosed fashion should be the preferred method as many developed techniques and several specimen retrieval bags for this method have been widely available. Nonetheless, in patients with suspicion for occult uterine malignancy after an appropriate preoperative evaluation, morcellation should be avoided (45). In those cases, alternatives such as minilaparotomy or vaginal retrieval of the uterine specimen are more reliable options.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…The FDA's April 2014 statement [6,7], published following the incidental morcellation of the uterine leiomyosarcoma, efficiently supplanted minimally invasive procedures associated with use of power morcellation, including LSH, in the United States (US) [8,9]. In other countries, the power morcellation and LSH are commonly performed [10].…”
Section: Introductionmentioning
confidence: 99%